2011
DOI: 10.1104/pp.110.171595
|View full text |Cite
|
Sign up to set email alerts
|

Proteins of Diverse Function and Subcellular Location Are Lysine Acetylated in Arabidopsis    

Abstract: Acetylation of the «-amino group of lysine (Lys) is a reversible posttranslational modification recently discovered to be widespread, occurring on proteins outside the nucleus, in most subcellular locations in mammalian cells. Almost nothing is known about this modification in plants beyond the well-studied acetylation of histone proteins in the nucleus. Here, we report that Lys acetylation in plants also occurs on organellar and cytosolic proteins. We identified 91 Lys-acetylated sites on 74 proteins of diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
316
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(339 citation statements)
references
References 63 publications
19
316
4
Order By: Relevance
“…Conversely, phosphorylated proteins were mainly localized to the nucleus and cytosol. Lys-acetylated proteins were localized in several cellular compartments in agreement with previous findings regarding a broad range of functions for this modification (37,38).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Conversely, phosphorylated proteins were mainly localized to the nucleus and cytosol. Lys-acetylated proteins were localized in several cellular compartments in agreement with previous findings regarding a broad range of functions for this modification (37,38).…”
Section: Resultssupporting
confidence: 79%
“…2B). Even though we identified more Lysacetylation sites than previous plant acetylproteome studies (37,38), it is important to mention that iTRAQ can interfere with the Lys-acetylation immunoprecipitation efficiency, as previously reported (39) and this can reduce the number of identified Lys-acetylated peptides. The distribution of the 603 phosphorylation sites identified in the exocarp, and the 878 sites detected in the mesocarp was, respectively 89%/92% ( p S); 10%/7% ( p T); and 1%/1% ( p Y) (Fig.…”
Section: Resultsmentioning
confidence: 44%
See 1 more Smart Citation
“…Two recent studies identified the first organellar Lysacetylated proteins in Arabidopsis (Finkemeier et al, 2011;Wu et al, 2011). Among these proteins were several plastidial proteins but only a few mitochondrial proteins, such as cytochrome c, the a subunit of the ATP synthase complex, and AAC1.…”
Section: The Aac Carriers As Well As the Atp Synthase Complexes Are Tmentioning
confidence: 99%
“…In plants, Lys acetylation was, until recently, mainly thought to occur on histone proteins as regulatory mechanism for transcription and chromatin functions (Hollender and Liu, 2008). However, several central metabolic enzymes of diverse subcellular compartments were recently discovered to be Lys acetylated in Arabidopsis (Arabidopsis thaliana), and in vitro deacetylation tests confirmed that Lys acetylation affects enzyme activities and protein functions (Finkemeier et al, 2011;Wu et al, 2011). Although even organellar-encoded proteins, such as the b subunit of the ATP synthase and the large subunit of Rubisco, have been identified as Lys acetylated in Arabidopsis, it is as yet unclear which enzymes regulate this modification in mitochondria and chloroplasts of plants.…”
mentioning
confidence: 99%